Colliding epistemologies, productive tensions and usable pasts in the generation of heritage-led immersive experiences. Issue 2 (1st February 2021) - Swords, Jon; Nally, Claire; Rogage, Kay; Watson, Richard; Charlton, James; Kirk, David
ABSTRACT: The growth of immersive technologies offers new ways in which heritage can be made usable. Virtual, augmented and mixed reality experiences are the latest media forms through which historical narratives can be told and heritage experienced. There are many challenges to create experiences which engage users in a meaningful way from the origination stage, through design and content creation to delivery, all of which bring together practitioners from disparate fields. Drawing on the concept of usable pasts, this article examines how disciplinary differences create tensions, challenges and productive outcomes in the generation and design of immersive experiences intending to take heritages out of museums to allow publics to experience them within the built environment. We draw on Brown and Knopp's approach of productive tensions and colliding epistemologies which helps highlight and understand the constraints and opportunities of cross-disciplinary work in the creation of usable pasts. Through our exploration of how to develop a design methodology for producing heritage-led immersive experiences we argue for the importance of understanding the philosophical approaches used by different stakeholders in the design process, highlight the importance of non-digital technologies and discuss how practical issues can produce ontological clashes.